HOW TO UNTIE “KOSOVO KNOT“? INTEGRATIVE APPROACH TO THE SERBIAN-ALBANIAN CONFLICT - Mojašević, Aleksandar (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
This paper presents Mnookin's conceptual framework for identifying and overcoming obstacles to the efficient and fair resolution of individual and group conflicts and disputes. This is followed by review of the basic elements of the negotiations between the Republic of Serbia and the self-proclaimed Republic of Kosovo, a summary of the results of those negotiations, as well as the views of Serbian public opinion on the declaration of independence of the so-called Kosovo and the Kosovo issue in general. After that, the basic elements of two well-known theories of intergroup conflict are presented in order to shed light on the nature of the conflict between two ethnic groups (Serbs and Albanians). Finally, the previous negotiations of the two parties are placed in the presented conceptual framework of negotiations, in order to identify the key points of contention in the previous negotiations of Serbia and the so-called Kosovo and offering potential solutions for overcoming them based on the presented theoretical model of negotiation in the presence of a third party (mediator). The key finding is that the negotiations can be concluded with a fair agreement, but only if the real (material) interests of the two parties are respected, but primarily the emotional ones, that is, those arising from the nature of the conflict between the social identities of the two ethnic groups.
Keywords: Serbia; so-called Kosovo; negotiations; obstacles; mediator; group conflict